Betel leaf yield in relation to soil fertility in Guntur district (Andhra Pradesh) - K Sireesha, B T Priya, P R Devi (Journal of Spices and Aromatic Crops, 2013)
An attempt was made to survey betelvine gardens in Guntur district of Andhra Pradesh to ascertain soil fertility status and its impact on growth and yield of betelvine. All the soils were clay loam in texture. The pH of the soil was alkaline (7.1 to 8.4) and EC ranged from 0.35 to 1.61 dSm-1. The organic carbon (OC) content of the soil was in the range of 0.55 to 1.24%. The available nitrogen (N), phosphorus (P) and potassium (K) status ranged from 201 to 313, 10 to 60, 337 to 840 kg ha-1, respectively. Correlation indicated that the growth parameters viz., number of laterals, intermodal length, petiole length and soil parameter viz. pH, EC and P were positively correlated with betel leaf yield but relations were not significant, whereas, plant height and soil nutrients viz., OC content, N and K were significantly and positively correlated with leaf yield.